Global scientific research on elderly malnutrition：A bibliometric analysis - Tian, Hua; Chen, Jie (Progress in Nutrition, 2022)
Background: The malnutrition in older adults increases rapidly with the accelerating development of the global aging. Malnutrition was considered to be a public health problem characterized by multifactorial physiological state. Bibliometric analysis and visualization to this field in the past 30 years may provide profound insights.Methods: Scientific citation index database was identified publications with author name, affiliation and origin country from 1991 to 2021 in this field, and systematically compiled the corresponding bibliometric data. Web of science database and excel were used to analyze generally, while VOSviewer and Citespace were used for bibliometric analysis and visualization.Results: In total, 2239 publications were found. The total number of publications increased substantially and exponentially in recent years, suggesting that more and more researchers pay attention to this field. The most contributor is the United States, whereas the highest average citations is Switzerland. Bibliographic coupling, coauthorship, cocitation, and co-occurrence analyses revealed that nutrition dietetics was the most research area. Vrije Universiteit Amsterdam and journal of Nutrition Health & Aging were the most contribution institution and journal. The publication in the Journal of the American Geriatrics Society by Kaiser MJ et al in 2010 had the most cited frequence. Co-occurrence analysis showed that the most research topics included “programming” “sarcopenia” “prevention” “risk” “nutrition support” “deglutition”.Conclusions: Through the visual analysis of publication in recent 30 years, we found the publication trends and research characteristics in this field. These findings will hopefully provide new insight into the study of elderly malnutrition.Implications for Practice: Malnutrition in older adults leads to heavy burdens to the individual, social and economic. Relevant professionals, such as doctors, nurses, psychologists and many other health practitioners, should raise broad awareness and attention to the research hot spots and frontiers of this topic, in order to promote the screening, evaluation, diagnosis and grading treatment for malnutrition in elderly people with different health and functional states.